Efforts Of Application Of Work Discipline In Improving Employee Performance At The State Court Of Karawang 1b - Nurul Maulidia; Sungkono; Maman Mulya Karnama (Enrichment : Journal of Management, 2022)
Employees are an important factor in every organization both to achieve goals effectively and efficiently. In achieving the success of the agency, it requires good and optimal performance. The purpose of this paper is to find out how the performance of employees of the Karawang District Court 1B. The District Court of Karawang 1 B is an accredited official body or agency, and implements a court system in the form of examining, adjudicating, and deciding cases. The District Court is a judicial institution within the general judiciary which is domiciled in the district or city capital. There are so many various cases handled by the Karawang District Court, ranging from cases of application for change of name, heirs and so on. That the performance of employees at the Karawang District Court 1B is in a good and satisfactory condition, because the average employee performance achievement obtained is close to the expected achievement target value.